Pengaruh Penerapan Bea Keluar Biji Kakao Terhadap Daya Saing Serta Ekspor Produk Kakao Indonesia - Maria Trisanti Saragih; Harianto Harianto; Heny Kuswanti (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2021)
The development of Indonesia's cocoa beans before the export duty policy shows that almost 90 per cent of cocoa beans exports were exported from total production which leads Indonesia as one of the biggest cocoa beans exporters in the world. However, on the other side, the cocoa exports to destination countries cause the domestic stock of raw materials for cocoa beans Domestic stock has decreased. Therefore, Indonesian government implements a cocoa bean export duty policy. This research aimed to analyze the effect of export duties policy on the competitiveness and exports of Indonesian cocoa products to export destination countries. Revealed Comparative Advantage (RCA) method is used to measure competitiveness, while Fully Modified Ordinary Least Square (FMOLS) is used to analyze the long-term effect of export duties on cocoa beans on competitiveness and exports of cocoa products. Based on the analysis result, all cocoa products have competitiveness. Indonesian cocoa butter has the highest competitiveness in export destination countries. Export duties policy has a long-term effect on competitiveness and exports of cocoa paste and powder but have no long-term effect on competitiveness and exports of cocoa butter.